Orbital radiographic anatomy. Part 1. The osseous orbit and its apex - O. Yu. Yatsenko; I. E. Tyurin (Вестник рентгенологии и радиологии)
Objective: to study the characteristics of the osseous orbit and its apex in health.Material and methods. The computed tomography scans of 210 individuals (266 orbits) without orbital disease were examined.Results. The paper presents linear indicators (horizontal input, vertical input, length) of the osseous orbit and its apex in health. It is emphasized that the volume of the osseous orbit and its apex in healthy men and women has statistically significant differences. Individual asymmetry of osseous orbital volumes in health was detected in 80.95% of the men and in 82.85% of the women; asymmetry of orbital fat volume was in 47.61% of the men and in 51.42% of the women.Conclusion. The asymmetry of the mean normal osseous orbital volumes in the population is only within the margin of statistical error. At the same time the individual asymmetry of osseous orbital volumes in health is as much as 3.0 cm3; that of osseous orbital apical volumes is not greater than 1.0 cm3. The linear and volume characteristics of the osseous orbit and its apex are useful in estimating the degree of clinical symptoms. These should be kept in mind in the differential diagnosis of true and false exophthalmos and these can also play a crucial role in choosing surgical tactics.